A university perspective on future food production - Ballard, Russ (New Zealand Science Review, 2010)
​​The Netherlands is generally regarded as the agri-food innovation leader in the northern hemisphere, while, half a world away, I like to think that New Zealand leads in the south. It is great news that Wageningen University has chosen Massey University to collaborate with on a project centred on protein studies that will tackle global food supply problems – and I am pleased that work on the foundations of that project, which is named ‘Proteos,’ has begun at the Riddet Institute.New Zealand has long been a land of milk and honey – even though we might well now phrase that as, mainly milk! Milk now earns >10 billion annually – and is growing steadily; honey is still earning <1 billion but is growing fast – watch this space! Seriously, our agricultural abundance has been our rock, the single most compelling comparative advantage we have, and still the brightest hope for our future growth.